2013
DOI: 10.1227/01.neu.0000430297.17961.f1
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Diverter Devices for Intracranial Aneurysms

Abstract: With the available data from the studies, both heterogeneity and publication biases imply that the current clinical use of FDDs is not supported by high-quality evidence. In the absence of reliable evidence, the use of FDDs in patients eligible for more conventional treatments should be restricted to controlled clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
125
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 42 publications
6
125
2
3
Order By: Relevance
“…The early morbidity rate of 8% is similar to the established 5%-7% seen in overall data, 9,10 and no aneurysm ruptures or delayed complications were observed among these data, whereas published data suggest a late morbidity of 3% and mortality of 1%. 10 Therefore, the overall safety profile of this small series appears grossly in line with the results of Pistocchi et al 1 and the overall published flow-diversion data.…”
Section: Discussionsupporting
confidence: 87%
“…The early morbidity rate of 8% is similar to the established 5%-7% seen in overall data, 9,10 and no aneurysm ruptures or delayed complications were observed among these data, whereas published data suggest a late morbidity of 3% and mortality of 1%. 10 Therefore, the overall safety profile of this small series appears grossly in line with the results of Pistocchi et al 1 and the overall published flow-diversion data.…”
Section: Discussionsupporting
confidence: 87%
“…9 Another review and meta-analysis of flow diversion demonstrated an all-comer late complication rate of 2.4%. 22 Few studies have subset analyses specific to cavernous segment aneurysms, but in a multicenter Italian study, Briganti et al 23 reported a 4% mortality rate for treatment of cavernous segment aneurysms with flow diverters, but this comprised 3 total cases (of 76): Two patients experienced fatal ICA thrombosis, and the other experienced a fatal ICA perforation, all during treatment of giant cavernous aneurysms. The mortality rate reported in the Italian study differs from that in both the subset analysis in the recent Canadian study 12 and in this series (both with 0% overall morbidity and mortality, 70 total combined cavernous aneurysms).…”
Section: Discussionmentioning
confidence: 99%
“…As reported in recent meta-analyses, early and late complication rates of the technique were not negligible. 2,6 At present, inhomogeneity of practices exists regarding intracranial arterial locations where flow diverters are considered safe for use. In the US flow diverters are FDA approved only for ophthalmic segments of the ICA.…”
Section: Supplementary Comparison With the Department's Series Of Stementioning
confidence: 99%